PCR-RFLP analysis of the Tams1 gene of Theileria annulata - Altay, Kürşat; Aktaş, Münir; Dumanli, Nazir (My University, 2007)
Tams1 is a merozoite surface antigen of Theileria annulata. Genetical variations of Tams1 make studies of vaccine and diagnostic tests like ELISA difficult. In this study, Tams1 genes of 89 T. annulata isolates obtained from natural infected cattle in Elazig and Bingöl regions were tested with PCR-RFLP. Six different restriction profiles (a, b, c, d, e, f) were detected. The number of restriction profiles of 89 samples was found to be as follows: 78(a), 2(b), 2(c), 5(d), 1(e), and 1(f).
Theileria annulata Tams1 geninin PCR-RFLP analizi.
Keywords: Animals; Antigens, Protozoan; Cattle; DNA, Protozoan; Polymerase Chain Reaction; Polymorphism, Restriction Fragment Length; Theileria annulata; Theileriasis; Turkey; parasite antigen; protozoal DNA; Tams1 antigen; unclassified drug; animal; animal disease; animal parasitosis; article; cattle; chemistry; genetics; immunology; isolation and purification; parasitology; polymerase chain reaction; restriction fragment length polymorphism; Theileria annulata; Turkey (republic)